THE RELATIONSHIP BETWEEN WORD CHOICE AND QUESTION-ANSWERING ABILITY IN 2-3 YEARS OLD CHILDREN - Sabrina, Isabel Selmiola; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study examines the relationship between word choice and question-answering ability in children aged 2-3 years. The research involved five participants: two aged 2 years and three aged 3 years. Data were collected through observation and structured tasks, where children were asked five types of questions (